A review: Exploring the role of ChatGPT in the diagnosis and treatment of oral pathologies - Payal Panwar; Shalini Gupta (Oral Oncology Reports)
This review article delves into the evolving landscape of artificial intelligence (AI), specifically focusing on the integration of ChatGPT in the domain of oral pathologies. ChatGPT, a language model powered by deep learning, has demonstrated significant potential in providing insights and support in various fields. Seeking the capabilities of ChatGPT, several researches have been explored in the context of ChatGPT's effectiveness in oral pathologies in this review article. In the context of oral health, the model's capabilities and limitations are scrutinized, offering a critical analysis of its current applications and future prospects in different sections of this review article.